REVITALISASI KEGIATAN MASYARAKAT BERBASIS PROGRAM KKN DI DESA KRETEK KROCOK BONDOWOSO - Miftahussalam; Miftahur Rahman (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
The focus of service activities aims to help students improve their ability to learn together with the community, apply integrated religious knowledge with technology, and help empower families and communities through religious development, application of knowledge and technology in the fields of entrepreneurship, education and skills. The method used is Community Development with the principles of enabling, empowering and protecting. Enabling creates productive and constructive situations so that society can develop. Empowering focuses on strengthening potential value in society. Protecting provides protection for marginalized communities. The results of the service state that the religious sector needs to be improved because it is an implementation of faith and devotion to Allah SWT. The education sector has a long-term mission to form a generation with strong character. The field of environmental cleanliness and health promotes a healthy environmental climate and culture. And the economy drives people's welfare.